Virtual Community For A Creative City - Przygodzki, Zbigniew; Kina, Ewelina (Quaestiones Geographicae, 2015)
Cities provide conditions for the development of creativity and creative capital; some cities have made it an area of strategic intervention. Surely, there is a strong link between the creativity of a city and the value of social capital in a given territory. Hence, it is vital to answer the following questions: To what extent does investment in human capital determine the value of creative capital? What to invest in? Can one invest efficiently taking advantage of the attractive and popular virtual space? These are the questions explored by the present authors. Their specific goal is to assess the importance of social networks as a modern ICT tool for establishing relations, and of open networks in the dissemination of knowledge and in the development of creative communities.